PENGEMBANGAN MEDIA DEKAK PADA MATERI FPB DI SEKOLAH DASAR - Mayang Pratiwi Sembiring; Nurjannah (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This study aims to produce Dekak learning media in mathematics learning of FPB material for Class IV students of SDN 101991 Bangun Purba and to determine the feasibility of Dekak learning media in mathematics learning of FPB material for Class IV students of SDN 101991 Bangun Purba which is valid from the results of feasibility validation by material experts, media experts and teacher responses. This research is a type of Research and Development (R&D) research with the 4D model developed by Thiagarajan (1974) which includes four steps, namely: define, design, develop, disseminate. But this research only limits to three stages, namely only up to the development stage. The subjects in this study were material expert validators, media experts and learning experts. The instrument used to collect data is a questionnaire. The data analysis technique used is qualitative descriptive analysis technique. The developed media was validated by one material expert, one media expert and one fourth grade teacher. Based on the assessment of the results of validation by material experts, Dekak products are suitable for grade IV students. Based on the assessment of the results of validation by media experts, Dekak products are very feasible to use for grade IV elementary school students and based on the assessment of the results of validation by learning experts, Dekak products are very feasible to use for grade IV elementary school students. So from the data from the validation results of the three validators it can be concluded that Dekak media in learning mathematics FPB material is declared valid and there are no revisions by experts, so it is declared very feasible to use as teaching materials in learning.